Risk-sharing and entrepreneurship - Matilda Kilström; Paula Roth (Research Institute of Industrial Economics (IFN), 2022)
In this paper, we study the role of risk-sharing in entrepreneurship-driven innovation. Studying entrepreneurship and innovation entails modeling an occupational choice and an effort choice. Risk-sharing may increase the number of individuals who become entrepreneurs by limiting the downside risk. The effort of entrepreneurs may, however, be hampered by high risk-sharing if this limits the returns faced by successful entrepreneurs relative to unsuccessful entrepreneurs. We construct a simple theoretical model where risk-sharing may be either private or provided through the welfare state by means of taxation. We show that, in addition to the occupational and effort choice dimensions, the level of public risk-sharing also matters for the characteristics of entrepreneurs.
Keywords: D64; E02; O30; O33; O43; O47; 330; Innovation; Institutions; Growth risk-sharing; Inequality; Incentives